Analisis Penerapan Prinsip Syariah di The Amrani Syariah Hotel Surakarta - Fazri, Nurul, Dr. Imron Rosadi, M.Ag (2017)
Sharia hotel is one of accommodation that uses the building to provide goods and services, such as providing lodging, food and drinking, and other services. These services managed for commercially purpose. Not only the accommodation has complied with the requirements set by the government, also the Islamic principles are added as operational based. Practically, sharia hotel should requires applying sharia principles to operate the business. This is a logical consequence for sharia hotel provider, not simply to gain the profit but to keep the sharia concept existence that is applied as business characteristic using Islamic concept. The purpose of this study is to know the application of sharia principle in The Amrani Syariah Hotel Surakarta. This research is field research uses descriptive qualitative approach. Data are collected from observation, hotels' documents, and interview with Manager The Amrani Syariah Hotel Surakarta. The data analysis uses deductive analysis method based on common rules to assess the practice of sharia principles on the research object that has been collected and described in descriptive explanation. The result of the study has showed that all sharia principles have been applied by The Amrani Syariah Hotel Surakarta by using sharia principle taken under Regulation of the Minister of Tourism and Creative Economy No. 2 of 2014 on Guidelines for the Implementation of Sharia Business Hotel. These regulations include the classification of sharia hotel business, evaluating certification of sharia hotel business, implementation of certification sharia hotel, the last development and control. There are two classifications sharia hotel business, first hilal-1, and second hilal-2. Each classification has own classification. The Amrani Syariah Hotel Surakarta is include the first classification hilai-1. The outline of these regulations contains various sharia principles derived from depth study of Islamic sharia that has relation with the practical business in the field hosptallity. The sharia principles were manifested in the absolute and not absolute form covering three aspects, there are products, services, and management. Therefore, there is correspondence between sharia principles that were applied by The Amrani Syariah Hotel Surakarta. Sharia concept has been taken through critical study of the argumentations related with sharia principles that should apply to the organizer hotel business as the user sharia system. Keyword : Sharia Principles, Regulation of the Minister of Tourism and Creative Economy No. 2 of 2014, Certification, Hilal (criteria of classification)